PERSEPSI PEMUSTAKA TERHADAP PROFESI PUSTAKAWAN DI PERPUSTAKAAN PUSAT UNIVERSITAS LANCANG KUNING PEKANBARU - Rismayeti, Rismayeti (Jurnal Ilmu Budaya, 2014)
This writing deals with the perception of library users to the profession of librarian in Perpustakaan Pusat Universitas Lancang Kuning Pekanbaru. The purpose of this study is to determine the perceptions of the library users to the profession of librarian. This analysis is done by applying descriptive qualitative method with incidental sampling techniques drawn from 575 populations of samplings. The results show that most respondents (76,47%) urge that librarian is a professional, besides, 77,65% respondents urge the librarians to have at least diploma certificate in library science. The analysis also shows that the salary affects the libarian's performances. Moreover librarians should provide good service, and involve in IPI as professional organization. At least, the librarian's attitude may contribute to their professions.